Sobolev regularity of the canonical solutions to $\bar{\partial }$ on product domains - Zhang, Yuan (Comptes Rendus. Mathématique)
Let $Ω $ be a product domain in $\mathbb{C}^n, n\ge 2$, where each slice has smooth boundary. We observe that the canonical solution operator for the $\bar{\partial }$ equation on $Ω $ is bounded in $W^{k,p}(Ω )$, $k\in \mathbb{Z}^+, 1